(untitled) (Current Horticulture, 2024)
The foliar spray of copper (0.3%) and znc (0.4%) solution at 15 and 25 days of growth improved the plant height, fresh weight and root size of radish (Raphanus sativus L.). The application of copper and zinc along with N, P, K fertilizers improved crop growth more than the control. The concentration of 0.6% copper and 0.8% sinc showed some toxic effect and reduced growth of leaves and root but was better than the no application of Cu and Zn elements.